Characterization of the complete mitochondrial genome of Quasilineus sinicus Gibson, 1990 (Nemertea: Heteronemertea) and its phylogenetic implications. Issue 9 (2nd September 2022) - Shen, Chun-Yang; Xue, Wei; Pang, Chong; Alireza, Asem; Mao, Xiaonan; Han, Jiahui; Chen, Haonan; Fu, Chunzheng
Abstract: In this study, we sequenced and characterized the complete mitochondrial genome (mitogenome) of Quasilineus sinicus Gibson, 1990 (Heteronemertea, Nemertea) using Illumina sequencing technology. The circular mitogenome was 16, 358 bp in length and comprised 22 transfer RNA genes, 13 protein-coding genes, and two ribosomal RNA genes. Its overall base composition included 20.82% A, 41.06% T, 26.68% G, and 11.44% C; in fact, the mitogenome had a high A + T content of 61.88%. Furthermore, our phylogenetic analysis demonstrated that Paleonemertea, Pilidiophora, and Hoplonemertea were monophyletic groups, and Q. sinicus was most closely related to Iwatanemertes piperata .